Clinical characteristics and effectiveness of antiviral agents in hospitalized children with infectious mononucleosis in China: A multicenter retrospective study. Issue 3 (22nd September 2021) - Hu, Huili; Deng, Huiling; Bi, Jing; Xu, Yi; Li, Shuangjie; Xie, Yue; Sun, Xinrong; Wang, Dongmeng; Li, Xufang; Ouyang, Wenxian; Hu, Bing; Zhang, Yufeng; et al.
ABSTRACT: Importance: The clinical characteristics of infectious mononucleosis (IM) in Chinese children have not been evaluated in multicenter studies, and the effectiveness of antiviral treatment are controversial. Objective: To investigate the clinical characteristics of Chinese children with IM and current status of antiviral therapy for affected patients. Methods: Hospitalized patients with IM were enrolled between 2018 and 2020 in five children's hospitals in China. The clinical characteristics were compared among four age groups: <3 years, 3–<6 years, 6–<10 years, and ≥10 years. The clinical characteristics of IM and effectiveness of antiviral therapy were compared among patients receiving acyclovir (ACV), ganciclovir (GCV), and no antiviral therapy (i.e., non‐antiviral group). Results: In total, 499 patients were analyzed; most patients were 3–<6 years of age. The most common symptoms and signs included fever (100%), lymphadenopathy (98.6%), pharyngitis (86.4%), eyelid edema (76.8%), and snoring (72.9%). There were significant differences in rash, hepatomegaly, and liver dysfunction among the four age groups. Patients aged < 3 years had a lower incidence of liver dysfunction and a higher incidence of rash. Among the 499 patients, 50.1% were treated with GCV, 26.3% were treated with ACV, and 23.6% received no antiviral therapy. Compared with the non‐antiviral group, patients in the ACV and GCV groups had longer durations of fever ( P < 0.001). There were no significant differences in the incidences of complications among the three treatment groups. Interpretation: The incidence of IM in Chinese children peaked at 3–<6 years of age. Clinical features of IM varied according to age. Patients receiving antiviral therapy exhibited more serious clinical manifestations than did patients without antiviral therapy. The effectiveness of antiviral therapy for IM requires further analysis.